1985
DOI: 10.1139/g85-101
|View full text |Cite
|
Sign up to set email alerts
|

Levels of conservation and variation of heterochromatin and nucleolus organizers in the Bovidae

Abstract: Chromomycin A3 banding of the mitotic sets of 10 species of Bovidae (cattle, wisent, yak, banteng, gaur, red buffalo, swamp buffalo, sheep, mufflon, and goat) serves to demarcate both centromeric constitutive heterochromatin and R-banding patterns capable of identifying all the chromosomes within a given complement. In all species significant amounts of chromomycin-bright heterochromatin are present at the centromeres of all autosomes, though there was a high degree of intra- and inter-individual variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
(13 reference statements)
2
20
0
Order By: Relevance
“…Similar results were obtained by Bianchi et al (1990) in acrocentric chromosomes of the moose. On the other hand, the narrow CMA 3 positive bands detected in the centromeric region of the X chromosome were similar to those observed by Mayr et al (1985 and in phylogenetically related species such as ibex (Capra ibex L.), chamois (Rupicapra rupicapra L.) and goat (Capra hircus L.).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar results were obtained by Bianchi et al (1990) in acrocentric chromosomes of the moose. On the other hand, the narrow CMA 3 positive bands detected in the centromeric region of the X chromosome were similar to those observed by Mayr et al (1985 and in phylogenetically related species such as ibex (Capra ibex L.), chamois (Rupicapra rupicapra L.) and goat (Capra hircus L.).…”
Section: Discussionsupporting
confidence: 81%
“…CMA 3 and DA/DAPI bind preferentially to GC-and AT-rich DNA regions, respectively, so it can be concluded that the bright chromosomal regions comprise these sorts of DNA. According to Mayr et al (1985), the centromeric regions of ovine autosomes contain GC-rich heterochromatin. However, we have found a heterochromatic fraction with lower GC concentration, which divides the positive fluorescent material of some elongated acrocentric chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…King (1980) and, later, other authors predicted that the differences in C-bands could be attributed to the addition or loss of heterochromatin; this process may be accompanied by chromosomal rearrangements such as fusions or fissions which would alter the morphology of the chromosome complement. Such types of changes have been described by Mayr et al (1985) in mammals and by John et a!. (1985) in grasshoppers.…”
Section: Discussionmentioning
confidence: 90%
“…A/u I/Hae Ill resistant chromatin Studies carried out on the chromosomes of different organisms show close correlation between C-band positive heterochromatin and regions that fluoresce differentially with DNA specific dyes (John et a!., 1985;Mayr et aL, 1985;Schmid et al, 1986). However, in contrast there is not a complete correspondence between C-band positive heterochromatin and chromosomal areas resistant to certam REs, since C-bands may or may not be attacked by a specific endonuclease in a number of organisms.…”
Section: Heterogeneity Of Constitutive Heterochroma Tinmentioning
confidence: 99%